Comparative Adsorption of Methyl Orange Color from an Aqueous Solution Using Activated Carbon - Al-Rub, Samer S. Abu; Alyami, Bandar A.; Alqahtani, Yahya S.; Alqarih, Alhassan R.; Dunquwah, Bader A.; Alyami, Mabar M.; Alghithan, Saleh K.; Alsalah, Hamad H.; Aburub, Aya S. (Indian Journal of Pharmaceutical Education and Research, 2024)
Background and Aim: The study was focused on the adsorption parameters of Methyl Orange dye (MO) onto Commercial Activated Carbon (CAC) in aqueous solution. The examined of parameters in the adsorption process were founded on the optimization. Materials and Methods: Langmuir, Freundlich and Timken models were studied at different temperatures. Time, pH, and adsorbent mass adsorption parameters were examined at 140 mg.L-1 MO dye concentration at 25ºC. PFO and PSO models were studied at 140 mg/L dye concentration. Results and Discussion: The adsorption capacity qe of AC was 42.6 mg.g-1 at 25ºC. Among the isotherm models studied, the Freundlich model was found to be the optimum model with adsorption process data. Parameters in the model were found to be 0.0054 L.mg-1 (KL), 12.76 mg.g-1 (qm), 0.7827 (R2) for the Langmuir isotherm model and.49 (1/n), 42.6 mg.g-1 (Kf), 0.0680 (R2) for Freundlich isotherm model and 33.12 mg.L-1 (A), 36.37 J.mol-1 (B), 0.7992 (R2) for Temkin isotherm model. Thermodynamic studies indicated that the adsorption process was exothermic. The adsorption enthalpy (ΔH) for MO dye was found to be -63248 KJ.mol-1. The negative value found for the (ΔG) indicated that adsorption of MO dye was spontaneous adsorption. The kinetic study of MO dye adsorption obeyed the Pseudo Second-Order (PSO) model. Conclusion: CAC is distinguished as an adsorbent that excels other adsorbents in removing the MO dye from aqueous solutions compared to the mentioned literature due to its chemical and physical properties.
Keywords: Methyl Orange (MO); Activated carbon (AC); Thermodynamics; Adsorption isotherm; models; Kinetics models